Analisis Ancaman Phishing Terhadap Penggunaan E-Commerce Di Indonesia - Al Fadillah, M Azmi; Ramadhan, Mochammad Guntur; Ariefiandi, Mohammad Erza (Journal of Informatic and Information Security, 2024)
This research investigates the threat of phishing in the context of e-commerce in Indonesia. Phishing is a fraud technique aimed at stealing sensitive information from users through various methods such as fake emails, counterfeit websites, and link manipulation. In Indonesia, the e-commerce sector accounts for 32% of phishing cases. The method used in this research is qualitative narrative analysis, employing data collection through literature review and distribution of questionnaires. The primary objective of this study is to raise user awareness of phishing threats, identify users' ability to recognize phishing indicators, and disseminate preventive approaches. The results of the study indicate that many users are still unaware of phishing indicators, making them vulnerable to attacks. However, the study also found that 53% of trained users were able to identify phishing sites. This research highlights the importance of user education and the implementation of security measures. Recommendations include ongoing training for users, the use of email filters, the implementation of digital fingerprint indicators, and the application of One Time Password (OTP) systems. In conclusion, to address the phishing threat in Indonesia's e-commerce sector, a combination of enhanced user awareness, the adoption of more advanced security technologies, and collaboration among various stakeholders is needed.